Pemanfaatan Teknologi Dalam Pendidikan Islam - Riska, Riska; Judrah, Muh.; Mustamir, Mustamir; aguswito, aguswito; Suriyati, Suriyati; Nur, Makmur Jaya (Dahzain Nur, 2025)
This study uses a qualitative approach with a descriptive research type. This approach was chosen to gain a deep understanding of the use of technology in the Islamic education process, both from the perspective of educators, students, and other supporting systems. Data collection was carried out through several techniques as follows: Observation: to directly observe how technology is used in learning activities, in-depth interviews: conducted with teachers, students, and institutional managers to explore perceptions, experiences, and challenges in the use of technology and documentation in the form of photos, policy documents, lesson schedules, or digital-based learning materials used in Islamic education. The collected data were analyzed using the Miles and Huberman analysis technique, namely through three stages: Data reduction: filtering and summarizing important data from the results of observations and interviews. Data presentation: compiling data in the form of descriptive narratives or tables. The results of the study can be concluded that the use of technology in Islamic education has brought significant changes in the learning process, both in terms of methods, media, and accessibility of Islamic information. Technology is an effective means of supporting learning that is more interactive, flexible, and in accordance with the needs of the times.